Geomagnetic activity and change of the baric field on the Akademik Vernadsky station - Sumaruk, Yu. P.; Sumaruk, P. V. (Ukrainian Antarctic Journal, 2008)
It was shown that in the region of the Antarctic station Akademik Vernadskiy there is seen inverse correlation between the dispersion of the atmospheric pressure and the geomagnetic activity. The dependence changes with the season and is better seen during the local winter.